1 PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN DI PREMIER BASKO HOTEL PADANG - Astuti, Puji; Kasmita, Kasmita; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2017)
This reseach aims to determine the effect of compensation towards employee performance at Premier Basko Hotel Padang. The compensation indicators are salaries, incentives, benefits and facilities. The employee performance indicators are general and personal skills, managerial skills, and departmental performance. The type of this research is descriptive quantitative, with population of all employees of Premier Basko Hotel Padang, totaling 106 employees. As for the number of samples in this reseach as many as 50 people. Sampling technique is purposive sampling, that is in taking the basic sample based on certain criterion. Data collection techniques were done by distributing questionnaires using Likert scale that has been tested for validity and reliability. Further data is analyzed through descriptive analysis with categorization method of assessment based on the average score and percentage of assessment. While the technique of data analysis using simple regression linear and hypothesis testing using statistical t test. The results showed average compensation variable is 4.37 with TCR of 87.4%. This means that compensation falling into the category of often given. Furthermore from the data processing can be seen that the average employee performance variable is 3.68 with TCR of 73.7%. This means that employee performance is included in good category. The hypothesis in this reseach knows that compensation has a significance value of 0.000, this can be interpreted that the compensation has a significant effect on the employees performance of Premier Basko Hotel Padang. While for the regression coefficient of variable compensation is 0.973 units. This means that if there is an increase in compensation of the unit it will increase the employee performance of 0.973 units. Keywords: Compensation and Performance